The ZOPP: as an instrument for project conceptualization and design - Mario Alberto, Mario Alberto (2013)
This document is a methodological profile, not a manual of the ZOPP Method (Ziel Orientierte Projekt Planung) or Objective Oriented Project Planning. It aims to present the relevant issues and concepts of the methodology in the process of conceptualization and design of a strategy, project or intervention for the solution of a problem.